A Report on nitrocellulose manufacture - Espejo, Manuel A.; Evora, Gordon D.; Sta. Maria, Angel D. Jr. (Diliman, Quezon City College of Engineering, 1963)
That the commercial production of nitrocellulose from bagasse for the plastics industry is feasible is stating too weakly the possibilities of such a venture. This design project points out that with a capital of P13.5 million, a nitrocellulose plant of 12,00 lbs. per day capacity could be expected to break-even at 36.5 percent of the production level, that pay-out time could be estimated as 4.12 years and that the percent return on investment woule be .1435. It may be very well said that the establishment of such a plant at the earliest possible time to take advantage of the absence of competition, would be most advisable.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Plastics plants; Nitrocellulose